Answer:
aₙ=5n-3
Explanation:
The nth term is given by the formula:
![aₙ = a₁ + (n - 1)d](https://img.qammunity.org/2023/formulas/mathematics/high-school/iqj5gva5pti652389af0lec04s060leovv.png)
where aₙ = nth term, a₁ = first term, n = the term number and d = the common difference
As a₁ = 2 and d = 4, the nth term is:
![aₙ = 2 + (n - 1) * 5](https://img.qammunity.org/2023/formulas/mathematics/high-school/iee6e1ljwdmwspqwvdpb9r53fbdnz24joc.png)
![\: \: \: \: \: = 2 + 5n - 5](https://img.qammunity.org/2023/formulas/mathematics/high-school/4y5njs143qzt47m2zqfth9occ2hoo70ubm.png)
![\: \: \: \: \: = - 3 + 5n](https://img.qammunity.org/2023/formulas/mathematics/high-school/skesjk12d4hmn7okxgfeaayj3dvxlh96no.png)
i like to write the positive integer first, but its up to you either way, so
aₙ=5n-3